EXPLORATION OF INDIGENOUS PLANT GROWTH PROMOTING FUNGI (PGPF) AS BIOLOGICAL CONTROL AGENTS AND BIOFERTILIZER - Asniwita, Asniwita; Novalina, Novalina; Syarif, M.; Bestari, Andini Vermita; Obura, Bruce Ochieng (LPPM Universitas Jambi, 2024)
This groundbreaking study ventures into uncharted territory to explore the vast potential of Plant Growth Promoting Fungi (PGPF) as multifaceted allies in agricultural sustainability. Departing from traditional paradigms, the research sets out to identify and characterize non-pathogenic fungal isolates with the capacity to serve as potent PGPF agents. Employing a pioneering approach, fungal isolates are meticulously collected from the rhizosphere of plants, heralding a new era of ecological exploration at the microorganism level. Rigorous testing for pathogenicity on soybean seeds unveils a rich reservoir of fungi diversity, with 18 isolates demonstrating remarkable efficacy in enhancing germination rates and promoting vigorous seedling growth. These findings not only underscore the pivotal role of PGPF in bolstering plant health and resilience but also herald a paradigm shift in sustainable agriculture. With the potential to serve as biopesticides for plant protection and biofertilizers for enhancing growth, these PGPF isolates offer a promising avenue for reducing reliance on synthetic inputs and mitigating environmental impacts. Moreover, their integration into integrated disease management strategies holds the promise of synergistic efficacy, paving the way for holistic approaches to agricultural sustainability. This research not only expands the frontiers of knowledge surrounding PGPF but also lays the groundwork for transformative innovations in agroecological practices, ushering in a greener, more resilient future for global agriculture.